Market Poultry: From Egg to Animal, Organic Poultry Production as a Livelihood-Based Social Enterprise for Urban Poverty Alleviation - Josephine Diana Campos; Jofrey Campos (Journal of Social Entrepreneurship Theory and Practice, 2025)
Urban poverty in Barangay 176-C, Bagong Silang, Caloocan City persists amid limited income opportunities and unstable livelihoods. This study examines how demographic factors—age, marital status, and number of children, affect socio-economic status and shape livelihood training preferences toward sustainable poverty alleviation. Using a quantitative-descriptive design and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were gathered from 100 adult residents representing diverse household types, including solo parents, informal workers, and unemployed adults. Results show that socio-economic status mediates the relationship between demographics and livelihood choices, with organic poultry production identified as the most preferred training due to its low cost, quick returns, and adaptability to urban settings. The study advances a family-mediated opportunity alignment model, extending the Capability Approach by illustrating how socio-economic realities and caregiving burdens influence enterprise decisions. Practically, the findings guide inclusive, market-driven livelihood interventions for community resilience and sustainable urban development